1996
DOI: 10.1017/s0022149x00015121
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerca fasciata: histochemical demonstration of succinate and NADH dehydrogenase

Abstract: The activities of selected enzymes of the respiratory chain system in Onchocerca fasciata (Filarioidea: Onchocercidae) have been investigated histochemically. Thus, the localization and distributions of NADH dehydrogenase (EC 1.6.99.3), succinate dehydrogenase (SDH) (EC 1.3.99.1) and cytochrome oxidase (EC 1.9.3.1) were investigated in various tissues of the adult female worm by employing MTT, Nitro BT (dehydrogenases) and DAB (cytochrome oxidase). Different tissues varied considerably in their enzymatic activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…By SEM, four levels of degeneration and calcification of worms were described. Omar and Raoof (1996) in Abha Province reported O. fasciata by histochemical investigated suggested that it lacks a classical, mammalian-type respiratory pathway and that oxidative phosphorylation is of no importance as an energy generating pathway in this essentially anaerobic parasite. Helmy and Al Mathal (2003) diagnosed three patients referred from Dermatology Out-patients Clinics, King Abdulaziz University Hospitals, as Sowda (chronic hyperactive form of O. volvulus).…”
Section: Introductionmentioning
confidence: 99%
“…By SEM, four levels of degeneration and calcification of worms were described. Omar and Raoof (1996) in Abha Province reported O. fasciata by histochemical investigated suggested that it lacks a classical, mammalian-type respiratory pathway and that oxidative phosphorylation is of no importance as an energy generating pathway in this essentially anaerobic parasite. Helmy and Al Mathal (2003) diagnosed three patients referred from Dermatology Out-patients Clinics, King Abdulaziz University Hospitals, as Sowda (chronic hyperactive form of O. volvulus).…”
Section: Introductionmentioning
confidence: 99%